1981
DOI: 10.1136/gut.22.6.445
|View full text |Cite
|
Sign up to set email alerts
|

Sulphasalazine and male infertility: reversibility and possible mechanism.

Abstract: SUMMARY Earlier observations on infertility related to sulphasalazine treatment were extended and semen samples obtained from 28 patients with inflammatory bowel disease on treatment with sulphasalazine at 2-4g per day. Semen was examined for changes in density, motility, and morphology before, during, and after withdrawal of sulphasalazine. Gross semen abnormalities were seen in 18 patients on this drug for more than two months. Semen quality improved after sulphasalazine had been withdrawn for more than two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
8

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(67 citation statements)
references
References 13 publications
1
58
0
8
Order By: Relevance
“…These findings are dose related and do not improve with supplemental folate [24]. Semen quality returned to normal 2-3 months after discontinuing sulfasalazine [25]. Therefore, it is advised that men with IBD on sulfasalazine considering conception should be switched to another oral mesalamine agent.…”
Section: Fertilitymentioning
confidence: 85%
“…These findings are dose related and do not improve with supplemental folate [24]. Semen quality returned to normal 2-3 months after discontinuing sulfasalazine [25]. Therefore, it is advised that men with IBD on sulfasalazine considering conception should be switched to another oral mesalamine agent.…”
Section: Fertilitymentioning
confidence: 85%
“…Sulphapyridine appears to cause oligozoospermia and has adverse effects on both sperm morphology and motility, but these effects are fully reversible upon drug cessation. Subsequent studies have consistently found not only improvements in sperm count, motility, and morphology but also successful conception after a switch to a different 5-ASA compound without the sulphapyridine component [Chatzinoff et al 1988;Cosentino et al 1984;O'Morain et al 1984;Riley et al 1987;Toovey et al 1981;Zelissen et al 1988]. However, a case of mesalazine-induced oligozoospermia in a young male with UC has been reported in Israel.…”
Section: Discussionmentioning
confidence: 98%
“…Past research showed that sulphasalazine causes oligozoospermia and has adverse effects on sperm morphology and motility [Cosentino et al 1984;Levi et al 1979;O'Morain et al 1984;Toovey et al 1981]. These effects are reversible, and semen quality can be restored after replacing sulphasalazine with mesalazine [Chatzinoff et al 1988;Riley et al 1987;Zelissen et al 1988].…”
Section: Introductionmentioning
confidence: 98%
“…As a result, Poisson analysis should find application in a variety of clinical conditions associated with asthenozoospermia, such as oligozoospermia or varicocoele, in permitting analysis of the penetrating ability of the spermatozoa in isolation from the defects in motility. Similarly, such analyses will permit a more effective interpretation of in-vitro fertilization data obtained after treatments which disrupt sperm motility, including cryostorage, ingestion of potential contraceptive agents such as gossypol (Aitken et al, 1983a) and sulphasalazine (Toovey, Hudson, Hendry & Levi, 1981), or in-vitro exposure to pharmacological reagents such as calmodulin inhibitors and adrenergic antagonists.…”
Section: Discussionmentioning
confidence: 99%